The Keneder Adler and Yiddish community life in Montreal, 1944 - Margolis, Rebecca (Canadian Jewish Studies / Études juives canadiennes, 2019)
Rabbi Pinchas Hirschprung became a towering figure in the Montreal Jewish community during a time when Yiddish functioned as the Jewish lingua franca. In 1944, The Keneder Adler both serialized his memoir, Fun Natsishen Yomertol: Zikhroynes fun a Polit (From the Nazi Vale of Tears: Memoirs of a Refugee) and printed it in book form. This study offers a snapshot of this rapidly changing community of 1944 through a close study of its newspaper, The Keneder Adler, including coverage of the liberation of the Nazi death camps, community responses, and new local community educational initiatives.